Analyzing rainwater chemistry at the continental GAW station Nagpur - SARKAR, JAYANTA; SONI, V. K.; GADGIL, A. S.; MUKHERJEE, A. K. (MAUSAM, 2006)
lkj & bl 'kks/k i= esa 1981 ls 1996 rd dh vof/k esa ukxiqj esa gqbZ o"kkZ ds ikuh esa jklk;fud rRoksa dh miyC/krk dk v/;;u fd;k x;k gSA bl v/;;u ls ;g irk pyk gS fd ukxiqj esa o"kkZ _rq esa ckj&ckj xtZ ds lkFk vkus okys rwQkuksa ds dkj.k o"kkZ ds ikuh esa Na+ vkSj Cl- ds lkanz.kksa esa leqnz dk izHkko de gSA ;gk¡ ij ekulwu _rq ds vkxeu ls igys ds eghuksa esa vkSj iwjh ekulwu _rq ds nkSjku NO3& esa cgqr vf/kd lkanzrk fjdkWMZ dh xbZ gSA ekulwu _rq ds nkSjku K+ dks NksM+dj o"kkZ ds ikuh ds lHkh ?kVdksa dh vxLr rd lkanzrk de gksrh tkrh gSA rFkkfi] flracj esa lHkh ?kVdksa dh lkanzrk esa o`f} ikbZ xbZ gSA Cl- vkSj Na+ ds fu{ksi.k eku rVh; dsanzksa dh rqyuk esa dkQh de ik, x, gSaA SO4&2 ds fu{ksi.k ekuksa dh rqyuk ;w- ,l- ,l- vkj- ds dqN Hkkxksa esa ik, x, ekuksa ls dh tk ldrh gSA o"kkZ ds ikuh ds fofHkUu ?kVdksa ds chp vuqikrksa dk v/;;u djus vkSj leqnz ds ikuh ds vuqikrksa ds lkFk mudh rqyuk djus ls irk pyk gS fd ukxiqj esa o"kkZ ds ikuh esa Na+ dh vf/kdrk dk dkj.k leqnz ds ikuh ds vykok vU; lzksr Hkh gSaA pH ekuksa esa cgqr vf/kd fofHkUurk ikbZ xbZ gSA ekulwu esa] twu ds ]ckn pH de gksrk tkrk gS vkSj flracj rd cgqr de gks tkrk gSA bldk dkj.k o"kkZ ds ikuh }kjk ewy dSVk;uksa dk i`Fkd djuk ekuk tk ldrk gSA vizSy vkSj ebZ ds lcls rst xehZ ds eghuksa esa pH dh vf/kd ek=k dk dkj.k okrkoj.k esa /kwy d.kksa dh ek=k] ftlesa eq[;r% ewy dSVk;u gksrs gSa] dks ekuk tk ldrk gSA ekulwu _rq ds izR;sd ekg ds pH ds v/;;u ls irk pyk gS fd twu vkSj tqykbZ esa o"kkZ dk Lo:i lokZf/kd ekSfyd gS tcfd vxLr vkSj flracj esa ukxiqj esa vEyh; o"kkZ dh dqN ?kVuk,¡ ns[kh xbZ gSaA tc ekpZ vkSj fnlcaj ds nks eghuksa esa pH dk eku 5-0 ls uhps fxj tkrk gS rc vEyh; o"kkZ dh leL;k cgqr vf/kd fodV gksrh gSA ekulwu iwoZ _rq ds nkSjku mPp lapkydrk ekuksa dk dkj.k bl vof/k esa okrkoj.k esa /kwy d.kksa dh vf/kd lkanzrk dks ekuk tk ldrk gSA ?kVdksa vkSj o"kkZ ds chp ds :Ik esa foijhr laca/k ik;k x;k gSA In this paper rainwater chemistry of Nagpur for the period 1981-1996, has been studied. The analysis reveals that at Nagpur rain water there is less marine influence on the concentrations of Na+ and Cl-. Pre-monsoon months, as well as the season as a whole, record higher NO3- concentration which could be attributed to frequent thunderstorm activities in this season. During monsoon months, concentration of all the constituents of rainwater, except K+, goes on decreasing till August. However, in September increase in concentration is observed for all the constituents. Deposition values of Cl- and Na+ are found to be quite low in comparison to that at coastal stations. SO4-2 deposition value is comparable to the values reported in some parts of USSR. Study of ratios between various constituents and a comparison with sea water ratios reveals that rainwater at Nagpur gets enriched in terms of Na+ from other sources besides sea water. pH values exhibited large variation. In monsoon, June onwards pH goes on decreasing and lowest value is obtained in September. This could be attributed to the preferential removal of basic cations by rainwater. In the peak summer of April and May higher values of pH could be attributed to the abundant prevalence of dust particles in the atmosphere chiefly consisting of basic cations. pH of individual months of monsoon season reveals that in June and July rainfall is predominantly basic in nature while in August and September some instances of acid rain has been observed at Nagpur. Acid rain problem seems to be more acute in the month of March and December when pH in these two months falls below 5.0. High conductivity values during pre-monsoon season could be attributed to higher dust concentrations in the atmosphere during this period. An inverse relationship of form Y = AR-B has been found between the constituents and rainfall.